Effect of Calcination Temperature on The Synthesis of Silica from Bagasse - Poedji Loekitowati Hariani; Fahma Riyanti; Desneli Desneli; Fatma Fatma; Sabila Yunita; Muhammad Said (The Journal of Pure and Applied Chemistry Research, 2021)
Bagasse is the solid waste derived from the sugar-making process. A large amount of silica in bagasse is a potential source of silica. In this study, extraction of silica from bagasse was carried out in the following steps: pretreatment of bagasse using HCl solution, followed by calcination at varying temperatures (700℃, 800℃, and 900℃) using a furnace. Furthermore, extraction using NaOH solution and precipitation using HCl. Silica characteristics were obtained using X-Ray Diffraction (XRD), Scanning Electron Microscopy-Electron Dispersive Spectrometry (SEM-EDS), and BET surface area. The results showed that calcination temperature affected the characteristics of the silica produced. The silica extracted at 700℃ produced an amorphous phase with a broad peak at an angle of 2θ = 20-24°. It contained the most considerable silica content and surface area, 42.46% and 796.89 cm2/g, respectively. The extracted silica had an average diameter of 5.67 mm and a pore volume of 1.184 cm3/g.